2009
DOI: 10.1111/j.1462-5822.2009.01346.x
|View full text |Cite
|
Sign up to set email alerts
|

How microbes utilize host ubiquitination

Abstract: SummaryActivity, abundance and localization of eukaryotic proteins can be regulated through covalent attachment of ubiquitin and ubiquitin-like moieties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 60 publications
0
38
0
Order By: Relevance
“…Ubiquitination of host targets is a prominent process utilized by pathogens to promote infection success (129). The bacterial effector AvrPtoB has similarities to eukaryotic E3 ligases and when secreted into host cells is able to interact with and ubiquitinate plant targets, including AtFLS2 (52, 114).…”
Section: Links Between Pattern Recognition Receptor Degradation and Ementioning
confidence: 99%
“…Ubiquitination of host targets is a prominent process utilized by pathogens to promote infection success (129). The bacterial effector AvrPtoB has similarities to eukaryotic E3 ligases and when secreted into host cells is able to interact with and ubiquitinate plant targets, including AtFLS2 (52, 114).…”
Section: Links Between Pattern Recognition Receptor Degradation and Ementioning
confidence: 99%
“…Although ubiquitination was initially characterized as a simple mechanism to target cellular proteins for degradation within the proteasome, it is now recognized as a far more complex mechanism that functions in a wide spectrum of processes. Perhaps not surprisingly, microbial (1) and viral (2,3) pathogens have learned to interfere with the host Ub machinery. The HIV-1 accessory proteins Vpu, Vif, and Vpr each interact with cullin E3 Ub ligase complexes, thereby allowing the virus to fine-tune and exploit the host Ub system for its own benefit (4).…”
mentioning
confidence: 99%
“…There are growing evidences showed that ubiquitination mediated by E3 ubiquitin ligase can not only regulate the development of immune system, but also initiate effective immune responses [4e6]. Furthermore, prokaryote may utilize the host ubiquitin system to invade, although prokaryote itself lacks classical ubiquitin system [7].…”
Section: Introductionmentioning
confidence: 99%